Diversity of Fruit Flies (Diptera: Tephritidae) Attracted by Methyl Eugenol in Carambola and Papaya Orchads in Malang Regency, East Java, Indonesia - Yogo Setiawan; Fatimah Hauroinsiyah; Fadel Muhammad Hamdoen; Mia Prastika Devi; Hagus Tarno (Plantropica: Journal of Agricultural Science, 2024)
Fruit flies (Diptera: Tephritidae) are among the significant pests in horticultural commodities. Methyl eugenol has been widely used for the detection, monitoring, and control of fruit fly worldwide. This study aimed to investigate the diversity of fruit flies attracted by methyl eugenol in carambola and papaya orchards in Malang Regency, East Java, Indonesia. Fruit flies were collected using modified plastic bottle traps, which were transformed into the Steiner trap model and attracted by methyl eugenol. The traps were placed in two study sites: papaya and carambola orchards. The results showed that three species of fruit flies were captured using methyl eugenol in this study: B. dorsalis, B. umbrosa, and B. carambolae. The most predominant species were B. dorsalis (86.02%), followed by B. carambolae (11.26%), and B. umbrosa (2.72%). Bactrocera dorsalis was the dominant species at both study sites.